2017
DOI: 10.1002/ep.12554
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic evaluation of standalone hybrid solar‐wind systems for small residential districts in the central desert of Iran

Abstract: Today, it is common knowledge that increased use of renewable energies has a significant impact on reducing greenhouse gas emissions. The most notable types of renewable energies are solar energy and wind energy, whose popularity comes from their prominent features such as cost‐effectiveness, stability and easy utilization. The objective of this paper is to perform a technical–economic analysis on combined utilization of solar and wind power in two cities of Qom and Yazd, to conduct a feasibility study on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 34 publications
(34 reference statements)
0
23
0
2
Order By: Relevance
“…Among renewable energies, the role of wind and solar energy is most remarkable for electrical production [40]. Because wind speed and solar radiation especially in the countries with proper potential in this regard are an effective factor to more exploitation of renewable energy and electrical production [34].…”
Section: World Potential Of Solar and Wind Energy For Electrical Prodmentioning
confidence: 99%
See 1 more Smart Citation
“…Among renewable energies, the role of wind and solar energy is most remarkable for electrical production [40]. Because wind speed and solar radiation especially in the countries with proper potential in this regard are an effective factor to more exploitation of renewable energy and electrical production [34].…”
Section: World Potential Of Solar and Wind Energy For Electrical Prodmentioning
confidence: 99%
“…More than two-thirds of Iran experience about 300 sunny days per year and average solar radiation of Iran is about 4.5-5.5 kw/m 2 per day, which points to a very high solar energy generation potential [20]. For example it can be mentioned that some of cities in Iran such as, Yazd [34], Taleghan, Abadan, Bandar-Abbas, Semnan [2], Kashan [33] has a good potential in solar energy. Also Iran country for good weather condition is suitable for wind energy utilization, and the abundance of windy areas in Iran provides it with a suitable platform to extend the development of wind farms.…”
Section: Solar and Wind Energy Potential In Iranmentioning
confidence: 99%
“…Razmjoo et al . performed technical–economic analysis of a solar and wind hybrid power in two cities of Qom and Yazd and found that the investments on renewable energy sector of both cities will be of economically justified.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed energy system is able to meet 67.3 and 62.3% load demand using renewable sources, which helps to reduce the GHG (greenhouse gas) emission by 67 and 64% for the two islands. Razmjoo et al [21] performed technical-economic analysis of a solar and wind hybrid power in two cities of Qom and Yazd and found that the investments on renewable energy sector of both cities will be of economically justified.…”
Section: Introductionmentioning
confidence: 99%
“…Although both mechanisms are within the mechanism of capillary pressure, capillary adsorption utterly depends on the surfactant formulation in comparison to the capillary snap-off. Two-dimensional presentation of foam system are being graphically depicted in Figure 1 (Jones et al, 2016a(Jones et al, , 2016bKapetas et al, 2016Kapetas et al, , 2017Khoshnevis et al, 2017;Li et al, 2006;Razmjoo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%